Hybrid Marriage Breakdown in Hamka’s Novel Merantau Ke Deli - ., Pardi; Nasution, Ikhwanuddin; ., Syaifuddin; Zein, T. Thyrhaya (KnE Social Sciences, 2019)
The two main characters in the novel, a man from Minang ethnic and a Javanese woman, meet and unite in a hybrid marriage institution, referring to the concept of combining two objects in one unit, part of a cultural hybrid and then analyzed through descriptive qualitative method reviewing the existence of marriage of different ethnics, part of a social problem in accordance with the function of literature as a medium for disclosure of social problems. Data and sources of data obtained are novels and words, phrases and sentences in the novel pointing to the discussion points. Tolerance, mutual understanding, solidarity, mutual support and not disputing cultural background are the main requirements in carrying out a hybrid marriage and all these requirements do not exist enough in the male character of this novel and eventually the marriage experiences a severe shock and ends in divorce. Disclosure of causal factors is the purpose of this study and the results are the norms of cultural traditions conveyed by a group of people and self-centeredness triggers the breakdown of the marriage. Keywords: hybrid, cultural tradition, self-centeredness, marriage breakdown